The Homeopathic Preparation Neurexan® vs. Valerian for the Treatment of Insomnia: An Observational Study - Rainer Waldschütz; Peter Klein (The Scientific World Journal)
Insomnia is prevalent and complementary therapies are common, but data are lacking on the effectiveness and tolerability of preparations beyond valerian. Here we report on an open-label, prospective cohort study in 89 German centers offering both conventional and complementary therapies. Subjects received the homeopathic preparation Neurexan® or valerian for 28 days. Doses were at physicians' judgments. Sleep duration and latency were evaluated based on patients' sleep diaries over 14 days; sleep quality was evaluated at 28 ± 1 days. A total of 409 subjects were enrolled. The groups were balanced at baseline for age, sex, weight, and sleep disturbances. At day 14, both groups reported improved sleep latency and duration; latency was reduced from baseline by 37.3 ± 36.3 min with Neurexan and by 38.2 ± 38.5 min with valerian. The duration of sleep increased by 2.2 (±1.6) h in the Neurexan group and by 2.0 (±1.5) h in the valerian group. Differences between the groups in improvement on sleep duration were significantly in favor of Neurexan therapy at days 8, 12, and 14. At day 28, quality of sleep was improved in both groups with no significant differences between the treatments. Significantly more patients reported lack of daytime fatigue with Neurexan than with valerian therapies (49% vs. 32%; p < 0.05 for the comparison). For patients favorable towards a CAM-based therapy, Neurexan might be an effective and well-tolerated alternative to conventional valerian-based therapies for the treatment of mild to moderate insomnia.